2005
DOI: 10.1007/s10549-004-3607-7
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 promoter polymorphism is associated with decreased breast cancer risk

Abstract: Interleukin-10 (IL-10) is an immunosuppressive cytokine which may facilitate development of cancer by supporting tumor escape from the immune response. A [TCATA] haplotype formed by polymorphisms at positions -3575, -2763, -1082, -819 and -592 in the promoter of the IL-10 gene is a strong determinant for IL-10 expression. The presence of this haplotype can be determined by analysis of the -592C > A polymorphism. Aim of the present study was to analyze the role of the IL-10 [TCATA] haplotype for breast cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
4
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 9 publications
5
38
4
1
Order By: Relevance
“…35,36,64,65 On the contrary, some other studies found GG genotype as a protective factor against breast cancer, 35,40 and other studies suggested that AA genotype plays a risk factor in breast cancer etiology. 39,40,42 According to the published literatures, only two studies conducted on Egyptian population and included only −1082G/A SNP in IL-10 gene promoter in breast cancer patients and they did not detect any significant difference in distribution of genotypes but the tumor size was significantly larger in breast cancer patients with AA genotype. 37 There are a number of recognition sites in the promoter of the IL-10 gene, including API, PEA1, and an ETS-like element.…”
Section: Discussionmentioning
confidence: 99%
“…35,36,64,65 On the contrary, some other studies found GG genotype as a protective factor against breast cancer, 35,40 and other studies suggested that AA genotype plays a risk factor in breast cancer etiology. 39,40,42 According to the published literatures, only two studies conducted on Egyptian population and included only −1082G/A SNP in IL-10 gene promoter in breast cancer patients and they did not detect any significant difference in distribution of genotypes but the tumor size was significantly larger in breast cancer patients with AA genotype. 37 There are a number of recognition sites in the promoter of the IL-10 gene, including API, PEA1, and an ETS-like element.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies show that high levels of IL-10 may actually be a risk factor for other cancers, hepatocellular, ovarian, melanoma, lymphoma, and myeloma (50). The IL-10 À592 C>A promoter polymorphism has been associated with a reduced breast cancer risk (37) and the IL-10 À1082 G>A polymorphism was associated with increased risk of noncardia gastric cancer (36). Currently, the role of IL-10 in cancer remains unresolved (53).…”
Section: Discussionmentioning
confidence: 99%
“…Data show that SNPs in the proinflammatory IL-1b, IL-6, and IL-8 genes and in the anti-inflammatory IL-10 gene result in changes in biological functions of the inflammation pathway and have been associated with a number of inflammatory diseases, including inflammatory bowel disease, arthritis, and Alzheimer's disease (29)(30)(31)(32)(33), as well as a number of cancers including colon, stomach, breast, and liver cancer and melanoma of the skin (34)(35)(36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…PCR reaction and evaluation of fluorescence data were done as described previously (14). For each set of reactions, one negative control containing water instead of DNA was added to check for contamination.…”
Section: Methodsmentioning
confidence: 99%